2013
DOI: 10.2308/ajpt-50663
|View full text |Cite
|
Sign up to set email alerts
|

Are There Adverse Consequences of Mandatory Auditor Rotation? Evidence from the Italian Experience

Abstract: SUMMARY Mandatory auditor rotation was recently proposed for the European Union and is also under consideration in the United States. There has been little research into either the benefits or costs of rotation in a true mandatory setting that could inform intelligent policy making. Our paper helps fill this gap by examining Italy, where mandatory rotation of auditors has been required since 1975. We find that outgoing auditors do not shirk on effort (or quality), but final-year fees are 7 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 27 publications
9
77
3
6
Order By: Relevance
“…Opponents to mandatory firm rotation also have a considerable amount of research to provide support for their perspective. Several studies (Arrunada & Paz-Ares, 1997;Cameran, Francis, Marra, & Pettinicchio, 2013;Daugherty, Dickins, Hatfield, & Higgs, 2012;Geiger & Raghunandan, 2002;Ghosh & Moon, 2005;Johnson et al, 2002;Mansi et al, 2004;Myers et al, 2003;Palmrose, 1987Palmrose, , 1991Petty & Cuganesan, 1996;Stice, 1991) propose that audit firm rotation is counterproductive due to the loss of specific client knowledge possessed by long-tenured audit firms. Jackson, Moldrich, and Roebuck (2008) found that when going concern was used as a proxy, firm tenure increased audit quality.…”
Section: Mandatory Audit Firm Rotationmentioning
confidence: 99%
“…Opponents to mandatory firm rotation also have a considerable amount of research to provide support for their perspective. Several studies (Arrunada & Paz-Ares, 1997;Cameran, Francis, Marra, & Pettinicchio, 2013;Daugherty, Dickins, Hatfield, & Higgs, 2012;Geiger & Raghunandan, 2002;Ghosh & Moon, 2005;Johnson et al, 2002;Mansi et al, 2004;Myers et al, 2003;Palmrose, 1987Palmrose, , 1991Petty & Cuganesan, 1996;Stice, 1991) propose that audit firm rotation is counterproductive due to the loss of specific client knowledge possessed by long-tenured audit firms. Jackson, Moldrich, and Roebuck (2008) found that when going concern was used as a proxy, firm tenure increased audit quality.…”
Section: Mandatory Audit Firm Rotationmentioning
confidence: 99%
“…Therefore, the 7 Other countries that also mandate auditor rotation are Italia and South Korea. Italia has enacted the regulation since 1975 (Cameran et al, 2015). European Union has also considered it even though it is still not enacted.…”
Section: Research Importancementioning
confidence: 99%
“…For example, a study in South Korea conducted by Kwon et al (2014) indicates that the audit quality did not change there. Meanwhile, investigation from other perspective conducted by Cameran et al (2015) shows that replaced auditor (or in its final year before rotation) does not decrease its audit quality. However, the audit fee is raised by 7% compared to previous years.…”
Section: Introductionmentioning
confidence: 99%
“…This need not be the case, as prior research has reported mixed results regarding the relationship between audit firm tenure and audit quality. 2 Evidence from Italy, the only EU Member State to apply an external rotation of audit firms previously, even indicates a decline in audit quality after the change in audit firm (Cameran et al, 2015;Cameran, Prencipe, & Trombetta, 2016).…”
Section: Mandatory Audit Firm Rotationmentioning
confidence: 99%